1995
DOI: 10.1128/jb.177.21.6153-6159.1995
|View full text |Cite
|
Sign up to set email alerts
|

Topology analysis of the colicin V export protein CvaA in Escherichia coli

Abstract: The antibacterial protein toxin colicin V is secreted from Escherichia coli cells by a dedicated export system that is a member of the multicomponent ATP-binding cassette (ABC) transporter family. At least three proteins, CvaA, CvaB, and TolC, are required for secretion via this signal sequence-independent pathway. In this study, the subcellular location and transmembrane organization of membrane fusion protein CvaA were investigated. First, a series of CvaA-alkaline phosphatase (AP) protein fusions was constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…On the other hand, CvaA* is encoded in frame with CvaA and is therefore identical to CvaA except that it lacks the hydrophobic N-terminal residues. CvaA* is therefore proposed to be a cytosolic protein (8,16,36). Using in vivo labeling experiments followed by fractionation of cells producing CvaA and CvaA*, we have confirmed that CvaA resides in the inner membrane whereas CvaA* is located in the cytosol (data not shown).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…On the other hand, CvaA* is encoded in frame with CvaA and is therefore identical to CvaA except that it lacks the hydrophobic N-terminal residues. CvaA* is therefore proposed to be a cytosolic protein (8,16,36). Using in vivo labeling experiments followed by fractionation of cells producing CvaA and CvaA*, we have confirmed that CvaA resides in the inner membrane whereas CvaA* is located in the cytosol (data not shown).…”
Section: Resultssupporting
confidence: 58%
“…Instead, this study shows that CvaA* stabilizes CvaA and this leads to increased ColV secretion. The C terminus of CvaA is predicted to reside in the periplasm (36). Therefore, a proposed stabilizing interaction of CvaA* with CvaA would probably not occur in the C terminus.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CzcC needs CzcB for its action, and it must handle the cations in cooperation with CzcB* or after the proposed CzcB*-funnelling process. CzcC might open up an escape route for the cations through the outer membrane; since CzcC is not a very hydrophobic protein (25), it might contact a hypothetical outer membrane protein, OmpY, as has been demonstrated for another transport process which involves a membrane fusion protein (34). Therefore, the zinc, cobalt, and cadmium cations might be transported across the cytoplasmic membrane by CzcA, through the periplasm by CzcB*, and across the outer membrane with the help of CzcC.…”
Section: Resultsmentioning
confidence: 99%
“…This systematic behavior can be used as an additional method to discriminate between fusions with a periplasmic or cytoplasmic PhoA moiety, but it is important that it is not used to normalize the activities. To demonstrate the synthesis of the fusion proteins, pulse and/or pulse-chase experiments are generally used (26,45,151,152,168,170,206,208).…”
Section: Enzyme Tagsmentioning
confidence: 99%